Le printemps silencieux comme expression paysagère du changement climatique dans nos villes ? - Philippe Woloszyn; Kahina Ikni; Elsa Alfonsi (Projets de Paysage)
In cities, climate change cannot be dissociated from the environmental question of the landscape. In this respect, the sound ecology of the landscape developed by Raymond Murray Schafer takes on its full meaning in the territorial sound experience shared by humans and non-humans. Since the 1970s Schäfer has raised awareness of the world of sound shared by the human and non-human features of the environment; the very process of perceiving sound and including it in our ordinary relationship with the environment has a name: soundscape. In order to capture all the spatial dynamics of this territorial sharing of human and non-human sound sources, we propose to apprehend the biophonic and anthropophonic qualities of the experienced environment—as defined by Bernie Krause (2016)—through the landscape and the spectrum of presence; an approach currently being tested in quiet areas such as woods, forests, parks and gardens in the metropolitan area of Bordeaux. This method of surveying and analysing the urban soundscape provides a ‘snapshot’ of the anthropophonic effects of rapid urbanisation and climate change. It provides a tool for conducting an ambient diagnostic of ‘sound sanctuaries’ within the city that need to be preserved or created to meet the acclimatisation needs of urban dwellers in situations of environmental stress. Eventually, the intention is for this ambient analytical model to evolve into a tool for observing and qualifying sound environments to study the potential status and use of these ‘quiet zones’ in the face of urban responses to climate change.